Literature Study of Specific Phobias (Nomophobia) from an Islamic Perspective - Hastuti, Novita Puji (Universitas Muhammadiyah Surakarta, 2022)
Purpose: Phobia is an anxiety disorder with symptoms of feeling afraid excessively of something usually not dangerous . Phobias can be experienced by anyone without looking at type gender, age, and social status economy . The purpose of this study is to describe one type of a specific phobia called Nomophobia from an Islamic perspective. The term NOMOPHOBIA or NOMObilePhonePhoBIA is used to describe a psychological condition in which the individual fears excessively regardless of cell phone connectivity. The term NOMOPHOBIA builds on the definition described in the DSM-IV, it has been labeled as